2003
DOI: 10.1111/j.1365-2567.2004.01768.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cAMP on the T‐cell response to type II collagen

Abstract: SUMMARYThere is considerable interest in the possible use of cAMP-elevating agents in the treatment of autoimmune diseases such as rheumatoid arthritis. The objective of this study was to evaluate the impact of different cAMP-elevating agents on the T-cell response to type II collagen within the context of collagen-induced arthritis, a murine model of rheumatoid arthritis. Spleen cells or lymph node cells from type-II-collagen-immunized DBA/1 mice were cultured in the presence of type II collagen plus one of ®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
2
14
0
2
Order By: Relevance
“…Thus, levels of cAMP may have changed from inhibitory to immunoenhancing. Moderate increases in cAMP have previously been demonstrated to increase the production of IL-4 and IL-5 in T cells (31). Further, cAMP-inducing agents increased the production of IL-6 and IL-10 in UVB-irradiated human keratinocytes (16).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, levels of cAMP may have changed from inhibitory to immunoenhancing. Moderate increases in cAMP have previously been demonstrated to increase the production of IL-4 and IL-5 in T cells (31). Further, cAMP-inducing agents increased the production of IL-6 and IL-10 in UVB-irradiated human keratinocytes (16).…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with our findings, Ozegbe et al recently reported a trend that low-dose PGE 2 enhances antigen-stimulated IL-5 production by mouse lymph node T cells. 64 In vivo, T cells are likely exposed to a wide range of levels of PGE 2 in a paracrine manner, depending on the intensity of local inflammation and the complement of infiltrating inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…IL-4 and IL-5 production was slightly upregulated at low concentrations of the cAMPelevating agents, and was modestly suppressed at the highest concentrations of cAMP-elevating agents (Ozegbe et al 2003). Experiments were then carried out to determine whether T cells were directly affected by cAMP-elevating agents or whether the immunomodulatory effects were mediated via APCs.…”
Section: Analysis Of the Immunomodulatory Effects Of Anti-arthritic Dmentioning
confidence: 95%
“…Pulsing T cells alone for a brief period with cholera toxin produced an almost identical effect to pulsing APCs alone, i.e. downregulation of proliferation, and downregulation of IFN-c production with little effect on IL-5 production (Ozegbe et al 2003).…”
Section: Analysis Of the Immunomodulatory Effects Of Anti-arthritic Dmentioning
confidence: 98%